1996
DOI: 10.1073/pnas.93.22.12428
|View full text |Cite
|
Sign up to set email alerts
|

Two glucose transporters in Saccharomyces cerevisiae are glucose sensors that generate a signal for induction of gene expression.

Abstract: Glucose is the preferred carbon source for most eukaryotic cells and has profound effects on many cellular functions. How Snf3p. We identified a dominant mutation in RGT2 that causes constitutive expression of several ILT genes, even in the absence of the inducer glucose. This same mutation introduced into SNF3 also causes glucoseindependent expression of ILT genes. Thus, the Rgt2p and Snf3p glucose transporters appear to act as glucose receptors that generate an intracellular glucose signal, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
426
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(443 citation statements)
references
References 26 publications
16
426
1
Order By: Relevance
“…It has recently been shown that sugar transporters can be involved in sugar sensing in yeast (Ozcan et al, 1996). Although evidence of such a role for VfSTPI and VfSUCI is missing, we have shown that VfSTPI and VfSUTI are highly homologous to other plant transporters responsible for sugar uptake.…”
Section: Transfer Cell Formation and Vfsutl Expression Are Lnduced Bymentioning
confidence: 65%
“…It has recently been shown that sugar transporters can be involved in sugar sensing in yeast (Ozcan et al, 1996). Although evidence of such a role for VfSTPI and VfSUCI is missing, we have shown that VfSTPI and VfSUTI are highly homologous to other plant transporters responsible for sugar uptake.…”
Section: Transfer Cell Formation and Vfsutl Expression Are Lnduced Bymentioning
confidence: 65%
“…In anaerobic glucose-limited chemostats, while glucose is efficiently transported and a sustained glycolytic flux is active inside the cell, the extracellular residual glucose concentration is low (,0.3 mM) compared to the K m of the high-affinity sensing systems (Ozcan et al, 1996;Rolland et al, 2000). This suggests that high levels of extracellular glucose are not required for stimulating Sfp1 activity.…”
Section: Discussion Continuous Cultures: Subsiding Growth Rate Effectsmentioning
confidence: 99%
“…For example the Escherichia coli narX and narQ genes encode transmembrane histidine kinases which act as external NO 3 − receptors and, in the presence of external NO 3 − or NO 2 − , activate transcription factors encoded by the narL and narP genes respectively (Merrick and Edwards, 1995). In budding yeast (Saccharomyces cerevisiae), transmembrane sensors for glucose, amino acids and NH 4 + have been identified and found to be homologous to membrane proteins that act as transporters for the respective nutrients (Klasson et al, 1999;Lorenz and Heitman, 1998;Ozcan et al, 1996).…”
Section: Localized Responsesmentioning
confidence: 99%